Vascular tissue engineering from human adipose tissue: fundamental phenotype of its resident microvascular endothelial cells and stromal/stem cells - Jeremy A. Antonyshyn; Meghan J. McFadden; Anthony O. Gramolini; Stefan O.P. Hofer; J. Paul Santerre (Biomaterials and Biosystems, 2022)
Adipose tissue is an abundant, accessible, and uniquely dispensable source of cells for vascular tissue engineering. Despite its intrinsic endothelial cells, considerable effort is directed at deriving endothelium from its resident stem and progenitor cells. Here, we investigate the composition of human adipose tissue and characterize the phenotypes of its constituent cells in order to help ascertain their potential utility for vascular tissue engineering. Unsupervised clustering based on cell-surface protein signatures failed to detect CD45–CD31–VEGFR2+ endothelial progenitor cells within adipose tissue, but supported further investigation of its resident CD45–CD31+ microvascular endothelial cells (HAMVECs) and CD45–CD31– stromal/stem cells (ASCs). The endothelial differentiation of ASCs altered their proteome, but it remained distinct from that of primary endothelial cell controls – as well as HAMVECs – regardless of their arterial-venous specification or macrovascular-microvascular origin. Rather, ASCs retained a proteome indicative of a perivascular phenotype, which was supported by their ability to facilitate the capillary morphogenesis of HAMVECs. This study supports the use of HAMVECs for the generation of endothelium. It suggests that the utility of ASCs for vascular tissue engineering lies in their capacity to remodel the extracellular matrix and to function as mural cells.